Vibration of thin rotating cross-ply laminated cylindrical shell with rings and stringers - Triyonoputro, Filipus Ferdian (2014)
A study on the vibration of thin simply-supported rotating cross-ply laminated cylindrical shell with axial and circumferential stiffeners, i.e. stringers and rings, is presented. The analysis is done using an averaging method whereby the properties of the stiffeners are averaged over the shell surface. Initial hoop tension, centrifugal forces, and coriolis forces due to the rotation of the shell are all considered in the formulation.